The effects of workforce diversity towards organizational creativity and the moderating role of knowledge sharing - Spran, Kannika Kannia; Mansor, Mohd Fitri; Mohd Kassim, Muhammad Asyraf (School of Technology Management and Logistics (STML), 2019)
In today’s globalize business environment, organizations face huge challenge in order to successfully survive in competitive market. As a significance, the organizations should continuously improve their performance in order to remain in competitive global market. There are several reason for the growing interest in creativity research. For innovation, creativity considered as fundamental for organizational performance and continuity in global market (Bodla, 2016). When the innovation process constantly demanding for novel solutions for products and service, creativity play an important role in merge and utilize diverse individual’s knowledge (Bouncken et al.,2016). The present study explore one of most current topic which is organizational creativity. In early 1990’s, the issue of organizational creativity received significant attention in many area of social science (Giustiniano et al., 2014). Organizational creativity refer to the creation of valuable and useful new products, service, ideas, procedures or process by individuals who working together in complex social system (Woodman et al., 1993). Organizational creativity serves as creative result of groups, not happen simultaneously with innovation, while it accomplished by gradual changes.